2018
DOI: 10.1177/1403494818801637
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in health during the Great Recession: A scoping review of the research literature

Abstract: Aims: The so-called ‘Great Recession’ in Europe triggered widespread concerns about population health, as reflected by an upsurge in empirical research on the health impacts of the economic crisis. A growing body of empirical studies has also been devoted to socioeconomic inequalities in health during the Great Recession. The aim of the current study is to summarise this health inequality literature by means of a scoping review. Methods: We have performed a scoping review of the research literature (English la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 97 publications
2
24
1
Order By: Relevance
“…In response to the financial crash of 2007 and the subsequent recession, many high-income countries including the UK responded with austerity policies; leading to cutbacks in many areas of public spending. [12][13][14] Between 2010/2011 and 2014/2015 UK departmental spending was cut by 9.1%. 15…”
Section: Increased Health and Social Care Pressuresmentioning
confidence: 99%
“…In response to the financial crash of 2007 and the subsequent recession, many high-income countries including the UK responded with austerity policies; leading to cutbacks in many areas of public spending. [12][13][14] Between 2010/2011 and 2014/2015 UK departmental spending was cut by 9.1%. 15…”
Section: Increased Health and Social Care Pressuresmentioning
confidence: 99%
“…The long-run improvement in all-cause mortality rates across most high-income countries has recently changed such that the rate of improvement has either slowed or reversed 1–7. Between 2012 and 2016 (inclusive) for women, an average annual decrease in life expectancy occurred in Northern Ireland of 1.2 weeks per year; and the rate of increase (in weeks of life expectancy per year) slowed to 0.1 in Iceland, 1.1 in England and Wales, 1.9 in the USA, 2.5 in Scotland and 2.7 in the Netherlands, from 8 to 12 weeks per year in the previous 5-year period.…”
Section: Introductionmentioning
confidence: 99%
“…The financial crash of 2007–2008, the resulting ‘great recession’, and the implementation of a variety of economic policy responses (including implementation of a fiscal stimulus in many countries up until around 2010, and subsequently ‘austerity’19 preceded the current change in mortality rate trends and have been suggested as the direct or indirect causes of the recent trends 1 8 20–22…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Studies also observed the widening socioeconomic inequalities regarding health during the economic crisis, indicating that economic shocks have a stronger impact on socioeconomically disadvantaged individuals. [9][10][11] Most preceding studies have compared population health during the pre-and post-crisis periods or focused on changes in population health during the crisis, 12,13 leaving the lingering impact of the economic crisis largely understudied. Difficulties in finding good jobs during the recession upon graduating from college and high school may have long-lasting adverse impacts on health in later life.…”
Section: Introductionmentioning
confidence: 99%
“… 5 8 Studies also observed the widening socioeconomic inequalities regarding health during the economic crisis, indicating that economic shocks have a stronger impact on socioeconomically disadvantaged individuals. 9 11 …”
Section: Introductionmentioning
confidence: 99%